2014
DOI: 10.1097/gme.0b013e3182947af3
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a sternal skin conductance criterion for measuring hot flashes in breast cancer patients

Abstract: This study provides evidence that a lower SCL criterion should be used to better detect objectively recorded hot flashes among breast cancer patients. Further work is needed to validate the proposed criterion among this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…

In their editorial, Carpenter and Yu 1 commented on our article, BRelationship between objectively recorded hot flashes and sleep disturbances among breast cancer patients: investigating hot flash characteristics other than frequency. 5 Besides, Carpenter and Yu questioned our use of hot flash parameters other than frequency based on their own work, which showed that sternal skin conductance intensity (magnitude) is not significantly correlated with subjective reports of bother and severity of hot flashes. Our sample was composed of women who had variable sleep quality.

…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…

In their editorial, Carpenter and Yu 1 commented on our article, BRelationship between objectively recorded hot flashes and sleep disturbances among breast cancer patients: investigating hot flash characteristics other than frequency. 5 Besides, Carpenter and Yu questioned our use of hot flash parameters other than frequency based on their own work, which showed that sternal skin conductance intensity (magnitude) is not significantly correlated with subjective reports of bother and severity of hot flashes. Our sample was composed of women who had variable sleep quality.

…”
mentioning
confidence: 99%
“…5 Besides, Carpenter and Yu questioned our use of hot flash parameters other than frequency based on their own work, which showed that sternal skin conductance intensity (magnitude) is not significantly correlated with subjective reports of bother and severity of hot flashes. These reservations are legitimate and expected, given that the new criterion challenges a long-established practice in this field.…”
mentioning
confidence: 99%